Location Information Assisted Joint Spectrum Sensing And Power Allocation For Cognitive Radio Networks - Thenmozhi, M.; B.Sridevi, Dr.; ., . (International Journal of Engineering and Technology, 2026)
The fifth generation wireless networks are expected to attain a thousand times higher capacity compared to the fourth generation wireless networks. Thus, raising the spectrum efficiency may be a crucial drawback, that should be thought of. cognitive radio is taken into account as an effective approach to alleviate the spectrum deficiency drawback. The goal of the paper is to enhance the output potency of data transmission and further to reduces the noise in wireless adhoc networks.There are two types of users in cognitive Radio network the users are classified into authorized Primary Users and unauthorized Secondary Users and there’s no dedicated channel to send data, sensors have to be compelled to discuss with the neighbors and choose a channel for data communication in CR-WSNs.PUs might arrive on the channel any time. If the PU claims the channel, the SUs need to leave the channel instantly. Therefore, data channels ought to be chosen showing intelligence considering the PU’s behavior on the channel and using some Priority based mostly choice algorithms. Our projected technique reduce the interference throughout data transmission between license and unlicenced medium.